Proceedings of the one day seminar on Opportunities & Challenges : facing malaysian education industry, 13 Jan. 1994, Kuala Lumpur Hilton - Seminar on Opportunities & Challenges : Facing Malaysian Education Industry (1994 : Kuala Lumpur); Challenger Concept (M) Sdn. Bhd.; Effective System Planner Sdn. Bhd. (Kuala Lumpur : Challenger Concept (M) Sdn Bhd., 1994)
44